Respuesta :

The value of the function is g(y - 9)=(y - 9)^2-7(y - 9)

How to evaluate the function g(y - 8)?

The equations of the functions are given as:

f(x)=-3/2x+11, g(x)=x^2-7x, and h(x)=|15-9x|

To evaluate the function g(y - 8), we make use of the function g(x).

So, we substitute y - 9 for x in g(x)=x^2-7x

The equation becomes

g(y - 9)=(y - 9)^2-7(y - 9)

Hence, the value of the function is g(y - 9)=(y - 9)^2-7(y - 9)

Read more about composite functions at:

https://brainly.com/question/13502804

#SPJ1

ACCESS MORE